2022
DOI: 10.2147/opth.s368634
|View full text |Cite
|
Sign up to set email alerts
|

24-Month Outcomes of Ahmed ClearPath® Glaucoma Drainage Device for Refractory Glaucoma

Abstract: Purpose To describe the safety and efficacy of the Ahmed ClearPath ® (ACP) 250 mm 2 glaucoma drainage device (GDD) in the treatment of refractory primary open-angle glaucoma (POAG). Patients and methods This was a retrospective, noncomparative, single-surgeon, interventional case series of adult patients with medically ± surgically refractory POAG undergoing ACP implantation. Intraocular pressure (IOP), the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Most recorded complications appeared early in the post-operative period and were self-limited, with no serious, sight-threatening complication recorded (Table 2). These results are in line with previously published series, although direct comparison is limited by our smaller sample size and the wide range of success criteria across the literature (Budenz et al, 2015(Budenz et al, , 2016Christakis et al, 2016;Dorairaj et al, 2022;Grover et al, 2022;José et al, 2022;Tan et al, 2022;Tsai & Budenz, 2017;Vallabh et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most recorded complications appeared early in the post-operative period and were self-limited, with no serious, sight-threatening complication recorded (Table 2). These results are in line with previously published series, although direct comparison is limited by our smaller sample size and the wide range of success criteria across the literature (Budenz et al, 2015(Budenz et al, , 2016Christakis et al, 2016;Dorairaj et al, 2022;Grover et al, 2022;José et al, 2022;Tan et al, 2022;Tsai & Budenz, 2017;Vallabh et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Two glaucoma drainage devices have been extensively studied: the Ahmed Glaucoma Valve FP7 (AGV) and the Baerveldt Glaucoma Implant (BGI) (Barton et al, 2011;Budenz et al, 2015Budenz et al, , 2016Christakis et al, 2016;Tsai & Budenz, 2017). Recently, two GDDs have been introduced in clinical practice, the Paul Glaucoma Implant (PGI) and Ahmed ClearPath (ACP) with early positive results (Dorairaj et al, 2022;Grover et al, 2022;José et al, 2022;Koh et al, 2020;Tan et al, 2022;Vallabh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because the suture fixation eyelets are positioned more anteriorly (Fig. 2), it was easier to place the scleral sutures while securing the ACP to the globe 7…”
Section: Discussionmentioning
confidence: 99%
“…Dorairaj et al [9] reported long-term safety and efficacy outcomes (24 months; mean last follow up 18 months) of the 250 mm 2 Ahmed ClearPath GDD in a retrospective, single surgeon, noncomparative, interventional case series that included 12 eyes of 11 patients with medically and/or surgically refractory POAG. A 58% reduction in mean IOP from baseline (29 mmHg) to last follow up (12.2 mmHg) was observed.…”
Section: The Ahmed Clearpath Devicementioning
confidence: 99%
“…Although the duration of 6 months of follow up in this study is short, the study characterized, for the first time, the safety and efficacy of the Ahmed ClearPath GDD, which were comparable to those of BGI as reported in landmark trials. Dorairaj et al [9] reported long-term safety and efficacy outcomes (24 months; mean last follow up 18 months) of the 250 mm 2 Ahmed ClearPath GDD in a retrospective, single surgeon, noncomparative, interventional case series that included 12 eyes of 11 patients with medically and/or surgically refractory POAG. A 58% reduction in mean IOP from baseline (29 mmHg) to last follow up (12.2 mmHg) was observed.…”
Section: Key Pointsmentioning
confidence: 99%